PENGARUH SENAM HIGH IMPACT DENGAN BEBAN TERHADAP PENINGKATAN KONSENTRASI BELAJAR MAHASISWA JURUSAN FISIOTERAPI POLTEKKES KEMENKES JAKARTA III - Mohammad Ali Ali; Abdul Rival Rival; Azis Ritonga Ritonga (Poltekkes Kemenkes Jakarta III, 2015)
Concentration is the power of thoughts and acts there is an object being studied and ignore everything that has nothing to do with the object being studied. Most educators and psychologists agree that the ability to focus on tasks is essential to improving achievement forstudents. To obtain these results, it is necessary that sufficient intake of energy for the brain in the form of glucose or lactate. One form of efforts to increase the adequacy of the intake is exercise or sport. One form of exercise can be a high impact exercises with weight training. The research method in the form of quasy experimental research, with sample of the population, namely the fourth generation students Department Physiotherapy Health Polytechnic Ministry of Health Jakarta III who has normal vital signs. Samples will be grouped into two groups, one group was given treatment group high impact exercise withweight training, and the second group was the control group without treatment. Data taken twice concentration examination before and after treatment using bourdon wiersma test. Results of hypothesis testing by independent T test results obtained p value = 0,008 with value α = 0,05, meaning that there is a significant difference in the increase in concentration between the treatment groups (exercise) with the control group (no exercises). In conclusion, from statistical test with a confidence level of 95%, there are significant differences in the average score of the concentration difference between respondents whose given high impact exercises with weight training (the case group) with no exercixe (the control group). At the group high impact exercises with weight training (the case group) have better level concentration.